Transcriptome Profiling of the Salt Stress Response in the Leaves and Roots of Halophytic Eutrema salsugineum - Li, Chuanshun; Qi, Yuting; Zhao, Chuanzhi; Wang, Xingjun; Zhang, Quan (Frontiers in Genetics, 2021)
Eutrema salsugineum can grow in natural harsh environments, however the underlying mechanisms for salt tolerance of Eutrema need to be further understood. Herein, transcriptome profiling of Eutrema leaves and roots exposed to 300 mM NaCl are investigated, and the result emphasized the role of genes involved in lignin biosynthesis, autophagy, peroxisome and sugar metabolism upon salt stress. Further, the expression of the lignin biosynthesis and autophagy related genes, as well as 16 random selected genes were validated by qRT-PCR. Notably, transcript abundance of a large number of lignin biosynthesis genes such as CCoAOMT, C4H, CCR, CAD, POD and C3’H in leaves were markedly elevated by salt shock. And the examined lignin content in leaves and roots demonstrated salt stress led to lignin accumulation, which indicated the enhanced lignin level could be an important mechanism for Eutrema responding to salt stress. Additionally, the differentially expressed genes (DEGs) assigned in autophagy pathway including Vac8, Atg8 and Atg4, as well as DEGs enriched in peroxisome pathway such as EsPEX7, EsCAT and EsSOD2, were markedly induced in leaves and/or roots. In sugar metabolism pathways, transcripts level of most DEGs associated with synthesis of sucrose, trehalose, raffinose and xylose were significantly enhanced. Furthermore, the expression of various stress-related transcription factor genes including WRKY, AP2/ERF-ERF, NAC, bZIP, MYB, C2H2, HSF were strikingly improved. Collectively, that increased expression of biosynthesis genes of lignin and soluble sugars, as well as genes in autophagy and peroxisome pathways suggested that Eutrema encountering salt shock possibly possess a higher capacity to adjust osmotically and facilitate water transport, scavenge ROS and oxidative proteins to cope with salt environment. Thus, this study provide a new insight for exploring salt tolerance mechanism of halophytic Eutrema and discovering new gene targets for genetic improvement of crops.